Introduction: The Arkhitekton - García, Patricia (Routledge, 2015)
Arising from the philosophical conviction that our sense of space plays a direct role in our apprehension and construction of reality (both factual and fictional), this book investigates how conceptions of postmodern space have transformed the history of the impossible in literature. Deeply influenced by the work of Jorge Luis Borges and Julio Cortázar, there has been an unprecedented rise in the number of fantastic texts in which the impossible is bound to space — space not as scene of action but as impossible element performing a fantastic transgression within the storyworld. This book conceptualizes and contextualizes this postmodern, fantastic use of space that disrupts the reader’s comfortable notion of space as objective reality in favor of the concept of space as socially mediated, constructed, and conventional. In an illustration of the transnational nature of this phenomenon, García analyzes a varied corpus of the Fantastic in the past four decades from different cultures and languages, merging literary analysis with classical questions of space related to the fields of philosophy, urban studies, and anthropology. Texts include authors such as Julio Cortázar (Argentina), John Barth (USA), J.G. Ballard (UK), Jacques Sternberg (Belgium), Fernando Iwasaki (Perú), Juan José Millás (Spain,) and Éric Faye (France). This book contributes to Literary Theory and Comparative Literature in the areas of the Fantastic, narratology, and Geocriticism and informs the continuing interdisciplinary debate on how human beings make sense of space.